The need for tawhidic epistemology - Hasan, Md. Mahmudul (IslamiCity, 2025)
Following in the footsteps of the Prophet, Muslims are required to seek knowledge that is beneficial for them and others and should avoid knowledge that is worthless or causes harm or leads to erroneous decisions or lifestyle choices. As long as the goal and purpose of knowledge seeking is the pleasure of God through righteousness, altruism, and beneficence, all branches of knowledge are good and Islamic. Thus, all academic fields are united and come under the purview of tawhidic epistemology.